THE EFFECT OF LONG-LASTING INSECTICIDAL NETS ON THE DYNAMICS OF MALARIA SPREAD IN INDONESIA - Aprianti, Euis; Jaharuddin, Jaharuddin (PATTIMURA UNIVERSITY, 2023)
Malaria is an infectious disease that can lead to death. Deaths from malaria globally have increased in 2020. So the spread of this disease is still a serious problem for society. The mathematical model used is the SIR-SI model, assuming that recovered individuals can be re-infected with malaria. Analysis was carried out on the effectiveness parameters of long-lasting insecticidal nets to determine their effect on the dynamics of the spread of malaria. The sensitivity analysis results showed that changes in the parameters of the effectiveness of long-lasting insecticidal nets had an inverse effect on the rate of spread of malaria. These results follow numerical simulations conducted using malaria case data in Indonesia (some assumptions). Thus, efforts can be made to suppress the spread of malaria by increasing the effectiveness of long-lasting insecticidal nets.